IMPROVING EFL SPEAKING SKILLS THROUGH TRADITIONAL LENGKO-LENGKO GAMES - Arviani, Vivin; Rahmiatin, Titin; Nasrullah, Rahmat; Indah, Tri Rusli (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Developing English speaking skills, particularly in fluency, comprehension, and vocabulary, remains a significant challenge for many English as a Foreign Language (EFL) learners, often compounded by low student motivation. This study investigates the efficacy of integrating a traditional game, Lengko-Lengko, as a culturally relevant pedagogical tool to address this issue. A one-group pretest–posttest pre-experimental design is employed with seventh-grade students (N=29, Class F) at a stated junior high school in Kendari. Quantitative data are collected through pre- and post-intervention speaking tests, assessed via a standardized rubric measuring fluency, vocabulary, grammar, and comprehension. Before conducting inferential analysis, a normality test using the Kolmogorov–Smirnov and Shapiro–Wilk methods indicates that both pre-test and post-test data are normally distributed (p > 0.05). The results also show a statistically significant improvement in overall speaking performance, with the mean score increasing from 23.31 (pre-test) to 33.97 (post-test), yielding a mean difference of 10.66 (p < .001). All assessed speaking sub-skills demonstrate notable gains, with vocabulary showing the highest improvement. These findings strongly suggest that the Lengko-Lengko game is an effective, engaging, and culturally grounded strategy for enhancing speaking proficiency in EFL classrooms. The study concludes by advocating for the incorporation of traditional games as interactive learning strategies to boost both motivation and oral communication skills.